A European survey of perendoscopic treatment of biliary complications in patients with alveolar echinococcosis. Issue 1 (2nd January 2017) - Ambregna, Sylvain; Koch, Stéphane; Sulz, Michael C.; Grüner, Beate; Öztürk, Sümeyra; Chevaux, Jean-Baptiste; Sulima, Małgorzata; de Gottardi, Andrea; Napoléon, Bertrand; Abergel, Armand; Bichard, Philippe; Boytchev, Isabelle; et al.
ABSTRACT: Background : Biliary complications represent a turning point in the course of Alveolar Echinococcosis (AE). We conducted a European survey to collect data on the current usage and results of perendoscopic interventions (PEIs) for their treatment. Methods : Patient's characteristics and follow-up until January 31st, 2015 were recorded using an online questionnaire. Results : From 18 centers 129 PEIs were analyzed in 38 patients; 139 plastic stents were inserted during 85 PEIs; median time between stent placements was significantly longer when 3 stents or more were placed. Initial symptoms disappeared in 95% and long-term bile duct patency was obtained in 73% of cases. Cholangitis was a more frequent complication of the PEIs (10%) than in other indications; intensive lavage of the bile ducts may prevent this complication. Conclusion : European centers use perendoscopic biliary drainage as an efficient and safe alternative to surgery to treat AE biliary complications. Insertion of multiple plastic stents delays stent occlusion and leads to effective and prolonged bile duct patency.